Evolution and Anticorrosion Properties of Ni-Cu Thin Film Coatings on Low Carbon Steel - Fayomi, O.S.I.; Popoola, A.P.I.; Adams, F.V. (Asian Journal of Chemistry, 2015)
Nickel-copper alloys electrolytic co-deposited on carbon steel and their recrystallization thermal permanence under various processed parameter were investigated. The influence of plating variables such as time of deposition, current, bath composition and pH on the coating properties, structural modification and electrochemical oxidation were investigated with the help of SEM/EDS and potentiodynamic polarization technique. The adhesion and strengthening behaviour on the coating was evaluated by diamond based Dura scan micro-hardness tester. The thermal stability was studied at 180 °C. From the result, modified morphology with perfect crystal growth was obtained. The corrosion resistance as well as micro-hardness of Ni-Cu alloy coatings improved significantly above the substrate and the annealed deposit. After thermal analysis, the surface structure of the deposited sample affirms the presence of pinhole which was attributed to the furtherance of oxidation process leading to internal cracks.